2007
DOI: 10.1128/iai.01619-06
|View full text |Cite
|
Sign up to set email alerts
|

Response of Leptospira interrogans to Physiologic Osmolarity: Relevance in Signaling the Environment-to-Host Transition

Abstract: Transmission of pathogenic Leptospira between mammalian hosts usually involves dissemination via soil or water contaminated by the urine of carrier animals. The ability of Leptospira to adapt to the diverse conditions found inside and outside the host is reflected in its relatively large genome size and high percentage of signal transduction genes. An exception is Leptospira borgpetersenii serovar Hardjo, which is transmitted by direct contact and appears to have lost genes necessary for survival outside the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
144
0
6

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 130 publications
(160 citation statements)
references
References 60 publications
10
144
0
6
Order By: Relevance
“…Expression of the gene encoding LA0572, predicted to be involved in transport of ferrienterobactin (55), and expression of the gene encoding LA2242, a desferrioxamine receptor homolog, were upregulated (Table 2), similar to what was found in L. biflexa (44). Expression of la2242 is also induced by transition from low to physiological osmolarity conditions (48) and exposure to serum (57).…”
Section: Resultssupporting
confidence: 56%
“…Expression of the gene encoding LA0572, predicted to be involved in transport of ferrienterobactin (55), and expression of the gene encoding LA2242, a desferrioxamine receptor homolog, were upregulated (Table 2), similar to what was found in L. biflexa (44). Expression of la2242 is also induced by transition from low to physiological osmolarity conditions (48) and exposure to serum (57).…”
Section: Resultssupporting
confidence: 56%
“…For pathogenic bacteria, osmotic stress can also serve as a signal that controls expression of virulence factors. Specifically, it has been suggested that sodium chloride concentration serves as a cue for the regulation of virulence in Listeria monocytogenes (10,20) and Leptospira interrogans (17). In keeping with this, a recent study showed that elevated salt concentrations result in alterations in expression of the virulence factor CagA in H. pylori strain 26695 (16).…”
supporting
confidence: 49%
“…No large-scale microarray data or extensive proteomic analyses have been reported for the saprophyte, although Thongboonkerd and colleagues compared total protein lysate of L. biflexa to multiple pathogenic strains to identify potential virulence factors (10). In contrast, extensive microarray and proteomic studies have been performed on various host-associated species (11)(12)(13)(14)(15)(16)(17)(18)(19)(20). These limitations in our basic knowledge of L. biflexa reduce its utility as a model organism, since there are no known protein markers for the outer membrane and no abundantly synthesized proteins have been reported.…”
mentioning
confidence: 99%